Problem solving skill of junior high school students on the solid geometry topic - F Rahmadeni; S Prabawanto; D Dasari (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to investigate problem solving skills of junior high school students in solid geometry (cube, cuboid, prism, and pyramid) topic. A descriptive qualitative research study through individual written test (essay) was conducted to described problem solving skill of junior high school students. A test was given to 32 students of ninth grade in one of junior high school in Bengkulu, Indonesia. The result show that almost all student difficult to: 1) make strategy to solve the problem, 2) use the strategy planned before to solve the problem. This result of the study conclude that junior high school students have a low problem solving skills. The result of this study show us the need for developing an efffective learning which can fasilitate students in improving their problem solving skill.